Strategic Public Relations Policy for Accelerating Hydrogen Acceptance: Insights from an Expert Survey in South Korea - Cho, Minhyuk; Lee, Youhyun; Kim, Youngjin; Lee, Min Chul (Energies, 2024)
Hydrogen has great growth potential due to its green, carbon-neutral nature, but public acceptance is low due to negative perceptions of the dangers associated with hydrogen energy. Safety concerns, particularly related to its flammability and explosiveness, are an obstacle to hydrogen energy policy. In South Korea, recent hydrogen-related explosions have exacerbated these concerns, undermining public confidence. This study developed public relations (PR) strategies to manage risk perception and promote hydrogen energy acceptance by analyzing the opinions of government officials and experts using SWOT factors, the TOWS matrix, and the analytic hierarchy process. The findings highlight the importance of addressing weaknesses and threats in PR efforts. Key weaknesses include Korea’s technological lag and the low localization of core hydrogen technologies, both of which hinder competitiveness and negatively impact public perception of hydrogen energy. Notable threats include deteriorating energy dependency and expanding global carbon regulations. This information can be used to influence attitudes and foster public acceptance of hydrogen energy policies. Emphasizing weaknesses and threats may result in more effective PR strategies, even if they do not directly address the primary concerns of scientific experts. The persuasive insights identified in this study can support future policy communication and PR strategies.
Keywords: Expert survey; Green carbons; Growth potential; Hydrogen Energy; Hydrogen policy; Hydrogen risks; Policy public relation; Public acceptance; South Korea; SWOT-AHP; expert survey; hydrogen policy; hydrogen risk; policy PR; SWOT-AHP